2018
DOI: 10.1007/s13197-018-3108-z
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage of refrigerated Litopenaeus vannamei: eavesdropping on Acinetobacter acyl-homoserine lactones promotes the spoilage potential of Shewanella baltica

Abstract: and are among the predominant spoilage bacteria in refrigerated shrimp (). are incapable of producing acyl-homoserine lactone (AHL) quorum sensing signals, but can respond to environmental AHLs. In this paper, was found to produce three AHLs, i.e. -butanoyl-l-homoserine lactone (C4-HSL),-(3-oxohexanoyl)-l-homoserine lactone (O-C6-HSL) and -(3-oxooctanoyl)-l-homoserine lactone (O-C8-HSL), according to thin-layer chromatography using the bioreporter A136. The agar diffusion and β-galactosidase assays revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…While it is difficult to fully define the causes of this phenomenon, the results obtained here suggested that P. fluorescens have the ability of utilizing non-secreted AHLs to regulate their growth. These findings agreed with those of Zhu et al (2018), who showed that exogenous AHLs can be utilized by S. baltica through the LuxR receptor to promote growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While it is difficult to fully define the causes of this phenomenon, the results obtained here suggested that P. fluorescens have the ability of utilizing non-secreted AHLs to regulate their growth. These findings agreed with those of Zhu et al (2018), who showed that exogenous AHLs can be utilized by S. baltica through the LuxR receptor to promote growth.…”
Section: Discussionsupporting
confidence: 91%
“…Cultures without P. fluorescens showed no significant AHLs depletion. Similarly, the determination of β-galactosidase by Zhu et al (2018) revealed that S. baltica could eavesdrop on the ambient AHLs produced by Acinetobacter , and AHL activity of pure Acinetobacter culture was significantly higher than that of the co-culture of S. baltica and Acinetobacter with an inoculation ratio of 1:1. Notably, the content of C 4 -HSL in P. fluorescens cultures did not change dramatically after incubation compared to that of C 14 -HSL, although C 4 -HSL plays the most important role in biofilm and protease experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies (Huang et al., 2018; Jia, Liu, et al., 2018; Wang et al., 2014; Zhuang et al., 2019) characterized the microbiota composition before sensory rejection point and found out that some bacteria (e.g., Acinetobacter ) could be dominant before spoilage, although its predominance was finally occupied by SSOs. These bacteria are expected to promote the spoilage potential of SSOs by QS or metabiosis (Zhu et al., 2018), although their real roles in fish spoilage need further explorations. To conclude, sampling time in microbiota research largely depends on the aim of the study.…”
Section: Methods and Technologies Used In Microbiota Characterizationmentioning
confidence: 99%
“…anthropi, P. aeruginosa, V. alginolyticus, V. parahaemolyticus, B. velezensis and Shewanella spp. Shewanella genus have been described among the predominant spoilage bacteria in refrigerated shrimp (Litopenaeus vannamei) (Zhu et al 2018). Burkholderia cepacia has also been isolated from marine environments (Alkhunni et al 2017).…”
Section: Discussionmentioning
confidence: 99%